Pemanfaatan AI dan Gamifikasi untuk Meningkatkan Kinerja Guru SDN 1 Sumber Agung: Pengabdian - Muhammad Nurwahidin; Riswandi Riswandi; Siti Mardasela; Agus Salim; Verawati Verawati; Larasati Larasati (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This article presents the results of a community service program focused on training teachers of SDN 1 Sumber Agung in the use of Artificial Intelligence (AI) and gamification to enhance teaching performance. The training included developing digital learning media using Canva, Wordwall, and Zep Quiz as practical examples of simple and applicable gamification strategies. The method was implemented through workshops, hands-on practice, and evaluation using teacher feedback questionnaires. The results indicate that teachers rated the training highly in terms of relevance, ease of use, and usefulness in improving creativity and classroom instructional effectiveness. The findings align with the TAM and UTAUT frameworks as well as gamification theories, which emphasize the role of perceived ease of use and perceived usefulness in technology adoption. Overall, the program significantly improved teachers’ digital competencies and fostered an innovative, technology-driven learning culture within the school.